2022
DOI: 10.7759/cureus.28395
|View full text |Cite
|
Sign up to set email alerts
|

Severe Congenital Diaphragmatic Hernia With Trisomy 9: A Case Report and Review of the Literature

Abstract: Congenital diaphragmatic hernia (CDH) is known to be complicated with various chromosomal abnormalities. However, the grade of pulmonary hypoplasia of CDH complicated by trisomy 9 is not known. This information is essential to the mother who has had a fetus with the same complication. We report a case of severe CDH with trisomy 9. The fetus had fetal growth restriction and multiple anomalies, including severe left CDH (observed/expected lung-to-head ratio 13.7%, liver-up, stomach grade 3 in Kitano classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We detected six P/LP CNVs in 79 fetuses with CDH, including mosaic trisomy 9, 13q14.11q31.2 deletion, 12p13.33p11.1 duplication, 8q22.2q23.3 deletion, 9q34.3 deletion and Xp22.31 deletion. It has been reported that trisomy 9, 8q23.1 deletion and 12p13.33p11.1 mosaic gain, which led to Pallister–Killian syndrome, are complicated by CDH 17,18 . 9q34.3 deletion (included EHMT1 gene) is regarded to cause Kleefstra syndrome, characterized by intellectual disability, autistic spectrum, hypotonia, and facial abnormality, and there are limited reports of prenatal phenotypes of recurrent 9q34.3 deletion, including increased nuchal translucency, coarctation of the aorta, and a short, thick corpus callosum 19 .…”
Section: Discussionmentioning
confidence: 99%
“…We detected six P/LP CNVs in 79 fetuses with CDH, including mosaic trisomy 9, 13q14.11q31.2 deletion, 12p13.33p11.1 duplication, 8q22.2q23.3 deletion, 9q34.3 deletion and Xp22.31 deletion. It has been reported that trisomy 9, 8q23.1 deletion and 12p13.33p11.1 mosaic gain, which led to Pallister–Killian syndrome, are complicated by CDH 17,18 . 9q34.3 deletion (included EHMT1 gene) is regarded to cause Kleefstra syndrome, characterized by intellectual disability, autistic spectrum, hypotonia, and facial abnormality, and there are limited reports of prenatal phenotypes of recurrent 9q34.3 deletion, including increased nuchal translucency, coarctation of the aorta, and a short, thick corpus callosum 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our case had CDH. Although it is unclear which extra part of chromosome 9 is pathogenic, some genes ( ABL1, TLN1, PLPP6 , and NOTCH1 ) have reportedly been associated with CDH as a de novo variant on chromosome 9 4,5 . Therefore, chromosome 9 may be associated with the pathological mechanism of CDH.…”
Section: Figurementioning
confidence: 99%